An economic review of the collaborative economy - Georgios Petropoulos (Bruegel, 2017)
The collaborative economy matches people online who want to share assets and services. This Policy Contribution - i) discusses how the collaborative economy can be defined; ii) provides an overview of evidence about its potential benefits for European economies and the impact of specific platforms in the sectors of their operation; iii) illustrates the criteria that enable professional and non-professional services offered through collaborative platforms to be distinguished; iv) recommends priorities for the platforms so that they can create a safe and transparent environment for the transactions of their users; v) discusses further regulatory concerns and how they should be approached. The collaborative economy is characterised by a great variety of business models. It spans multiple sectors each of which has its own market characteristics. A single definition is therefore beyond reach. However, a common element in the majority of business models is the use of under-utilised assets for the extraction of economic benefits. There is evidence that Europe could enjoy major economic gains from the collaborative economy, especially if barriers are removed and the regulatory framework is adjusted to better accommodate platforms. However, in particular sectors such as ride-sharing and short-term accommodation, the benefits from the operation of platforms come at a cost because platforms can have a detrimental effect on `traditional' incumbent operators. The technology is thus disruptive to many traditional businesses. While under EU legislation it is not clear when services supplied through collaborative platforms can be classified as professional, a careful examination of business models on a case-by-case basis can help to define some relevant criteria. The frequency with which a service is provided, the provider's motive and the associated remuneration are three important aspects that enable professional and non-professional services to be distinguished. As intermediaries, collaborative platforms have access to a large volume of information about the market and about their users, which is not available to other market participants or the regulator. Consumer protection requires a safe and transparent environment for transactions. Platforms based on their market position could be very helpful with this respect. Legal certainty and regulatory clarity are also required to incentivise further investment in efficient information technologies and platforms. The current uncertainty over the status of the collaborative economy platforms, legal disputes in national and European courts and decisions to restrict the operation of platforms at local/city levels create an environment in which it is difficult to attract new investment in Europe. Regulatory authorities should move quickly to define the framework of the operation of such platforms to restore investors' confidence. Local regulation is very important for defining the operational framework of collaborative platforms that can bring the greatest benefits to local economies. But an EU-wide approach is also needed to define the general framework of the operation of these platforms and to address in a decisive and clear way the associated regulatory concerns
Keywords: 330